Welding Fumes Exposure and the Risk of Head and Neck and Gastrointestinal Cancer: A Systematic Review and Meta-Analysis - Siea, Andrei Cosmin; Collatuzzo, Giulia; Hamdani, Maha; Boffetta, Paolo (La Medicina del Lavoro, 2025)
Background: The association between welding fumes and cancers other than lung cancer remains undefined. We conducted a systematic review and meta-analysis on occupational exposure to welding fumes and the risk of head and neck cancer (HN, comprising oral, pharynx, and larynx) and gastrointestinal cancer (GI, comprising esophagus, stomach, colorectal, liver, and pancreas). Methods: A systematic search was performed in PubMed, Scopus, and Embase using PRISMA guidelines. Cohort studies on occupational exposure to welding fumes were identified. Study quality was assessed through the CASP score. Data were analyzed in random-effects models to calculate the relative risks (RR) and 95% confidence intervals (CI) of HN and GI cancer overall and stratified by cancer site. Results: Seven independent studies with data on oral, pharynx, larynx, esophagus, stomach, colorectal, liver, or pancreas cancer were identified. We observed the following associations: HN RR=1.10 (95% CI 1.00-1.22); GI RR= 1.03 (95% CI 0.97-1.10); oral and pharynx RR=1.06 (95%, CI 0.93-1.20, eleven risk estimates); larynx RR=1.17 (95%, CI 1.01-1.37, nine risk estimates); esophagus RR=0.98 (95%, CI 0.83-1.15, three risk estimates); stomach RR= 1.10 (95%, CI 1.02-1.19, five risk estimates); colorectal RR=0.99 (95%, CI 0.85-1.15, seven risk estimates); liver RR=1.23 (95%, CI 0.79-1.90, five risk estimates); and pancreas cancer RR=1.05 (95%, CI 0.94-1.16, three risk estimates).Conclusions: We observed an association between occupational exposure to welding fumes and larynx and stomach cancer. No association was found for other HN or GI cancers. Our study stresses the need to investigate the risk of cancers other than lung following occupational exposure to welding fumes.